2017
DOI: 10.1016/j.ijid.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system infections in the absence of cerebrospinal fluid pleocytosis

Abstract: Previous multicenter/multinational studies were evaluated to determine the frequency of the absence of cerebrospinal fluid pleocytosis in patients with central nervous system infections, as well as the clinical impact of this condition. It was found that 18% of neurosyphilis, 7.9% of herpetic meningoencephalitis, 3% of tuberculous meningitis, 1.7% of Brucella meningitis, and 0.2% of pneumococcal meningitis cases did not display cerebrospinal fluid pleocytosis. Most patients were not immunosuppressed. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Moreover, classical meningitis symptoms were less frequent in the study patients without CSF pleocytosis. This finding is in line with previous reports showing that headache and neck stiffness are less frequent in older adults with CNS infections (Erdem et al, 2017;Wang et al, 2014). Furthermore, more than half of the patients without CSF pleocytosis underwent lumbar puncture within 1 day of symptom onset, and peripheral WBC counts were significantly lower in patients without pleocytosis.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, classical meningitis symptoms were less frequent in the study patients without CSF pleocytosis. This finding is in line with previous reports showing that headache and neck stiffness are less frequent in older adults with CNS infections (Erdem et al, 2017;Wang et al, 2014). Furthermore, more than half of the patients without CSF pleocytosis underwent lumbar puncture within 1 day of symptom onset, and peripheral WBC counts were significantly lower in patients without pleocytosis.…”
Section: Discussionsupporting
confidence: 92%
“…6 Cerebrospinal fluid (CSF) is abnormal in most cases though normal CSF has been reported in a few cases. 7 Skin lesions of brucellosis were associated with recurrent attacks of vasculitis, suggesting that the same mechanism can lead to stroke, as reported in one case. 8 Diagnosis of Neurobrucellosis relies on clinical features and imaging in the background of ongoing Brucella infection.…”
Section: Introductionmentioning
confidence: 55%
“…On the other hand, in one case series, 7% (4) of 52 cases of NTMM had normal CSF findings and the underlying condition in almost all of those cases was AIDS 2. It has been similarly reported that pleocytosis in tuberculous meningitis patients without HIV infection was found in 97% (488) of 507 patients,7 while normal CSF findings, defined as white cells<5/μL, protein<45 mg/dL and glucose>45 mg/dL, were reported in only 0%–4% of tuberculous meningitis patients with HIV infection 8. Since the degree of immunosuppression may affect intracerebral inflammation,9 10 normal CSF findings do not justify exclusion of mycobacterial CNS infection in immunosuppressed patients.…”
Section: Discussionmentioning
confidence: 88%